Contributions of Faik Konica in Enriching Vocabulary of Albanian Through Word Formation - Luniku, Rakela (Mediterranean Journal of Social Sciences, 2012)
Faik Konica had a genuine philological formation, and it seems in the way how we rigorously respected the law of linguistics.As a connoisseur of many excellent western language who has become an admirable job with the Albanian vocabulary, choosing it asone of the main ways to enrich the continuous vocabulary of the lexicon and its clearance from foreign word,word formation. His wordcreations are constructed so concise from the linguistic side, and sounds so beautiful in Albanian, that it regrets that has not survived thetime. It is enough to mention from his wonderful creations some of them in the local function, which: for the word chair he proposed"ndenjëse" , for the hospital he proposed the word "sëmurtore", for the library, the word "libërtore", etc, which prove the best of Konica'sefforts to maintain clean the mother tongue with replacing the foreign word with Albanian's corresponding. Despite, that this formationhave survived the time or not, one fact is important that Faik Konica felt the necessity of language for such formations and was put inthe forefront of his contemporaries, who trying to enrich as much as possible the Albanian language.